A Simple Approach to Teach Newton’s Third Law (Jurnal Pendidikan IPA Indonesia, 2020)
The results of previous researches indicated that there were problems with the mental model and students’ conceptual understanding of the action-reaction law (Newton’s third law, NTL). This research aimed to reveal the effect of a simple approach in teaching NTL. The research was conducted in the first-year of pre-service physics teachers at the Physics Education Department of Tadulako University. Research designs for three consecutive years were (1) one-group, pre-test, and post-test design, (2) a static group comparison (pre-test for the experimental group), and (3) a quasi-experimental. The approach used was an interactive demonstration that consisted of five phases, i.e: eliciting an intuitive argument, demonstrating a continuous force: pulling, demonstrating a continuous force: pushing, demonstrating impulsive force: collisions, and refining the concept with Elby’s pair. Data were collected using a multiple-choice test developed in previous research. The results of the data analyses showed that the approach could improve students’ understanding of the action-reaction law, supporting conceptual change by exhibiting N-gain in the moderate and high categories. The instructional design can be considered for implementation in learning in high schools, lecture on pre-service physics teachers and basic physics lecture, in general..